Etude du profil de résistance aux antibiotiques des germes responsables des infections des voies urinaires (IVU) - BELAALA Saida CHIA Samiha LADGHEM CHIKOUCHE Wafa REBIBI Mounira (Université Mohamed Boudiaf - M’Sila, 2024)
Among all tested UCB, 26.47% were positive. The predominant bacteria were Escherichia coli at 47.86%, followed by Enterobacter cloacae at 15.38%, Staphylococcus aureus and Staphylococcus saprophyticus at 9.40%, Pseudomonas aeruginosa at 8.55%, and Enterococcus faecalis at 3.42%. Regarding the results of antibiotic resistance analysis, Escherichia coli was the most resistant, followed by Enterobacter cloacae. Conclusion: The frequency of urinary bacteria and their resistance indicate that antibiotic treatment must be adapted based on up-to-date data on the incriminated germs, effective antibiotics and the patient health status.
Keywords: Urinary tract infections - Antibiotic treatment - Antibiotic resistance.